2003
DOI: 10.1093/jurban/jtg083
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevention Among Injection Drug Users: The Need for Integrated Models

Abstract: Opportunistic infections (OIs) were first recognized among injection drug users (IDUs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Counselors and other staff could include a history of incarceration in their clinical assessment, and use this as a marker for HIV risk. Peer-led prevention interventions, a successful approach among IDUs (Latkin 1998), could target previously incarcerated men, which would move the focus beyond the individual level to social network and community norms (Metzger and Navaline 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Counselors and other staff could include a history of incarceration in their clinical assessment, and use this as a marker for HIV risk. Peer-led prevention interventions, a successful approach among IDUs (Latkin 1998), could target previously incarcerated men, which would move the focus beyond the individual level to social network and community norms (Metzger and Navaline 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Over ten million (78%) live in developing and transitional countries (Eastern Europe and Central Asia, 3.1 mil-The most widely advocated approach for prevention of HIV transmission among drug users has been drug abuse treatment 10 . Early clinical trials have shown that methadone treatment reduces drug use although relapse is frequent 11 .…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…Several studies examined different types of targeted interventions to reduce sexual risks with varying results, but most achieving some level of success (Rietmeijer et al, 1996;Sterk et al, 2003). Nevertheless, in many of the studies, levels of unprotected sex remained high even with reductions (Dolezal et al, 1999), and despite the success of specific interventions, they have not been implemented on any large scale (Metzger and Navaline, 2003;Strathdee and Sherman, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of sexual behavior interventions among IDUs in the United States concluded that, while an overall moderate decrease in risk behaviors indicated that these interventions can lead to behavior change among IDUs, better programs with stronger effects are needed (Semaan et al, 2002). In addition, a review of sexual risk reduction interventions indicated that while some have found success, there has not been a concerted effort to implement these programs (Metzger and Navaline, 2003;Strathdee and Sherman, 2003).…”
Section: Discussionmentioning
confidence: 99%